2018
DOI: 10.3390/coatings8110378
|View full text |Cite
|
Sign up to set email alerts
|

Specific Features of Structure, Electrical Conductivity and Interlayer Adhesion of the Natural Polymer Matrix from the Layers of Branched Carbon Nanotube Networks Filled with Albumin, Collagen and Chitosan

Abstract: This paper considers the problem of creating a conductive matrix with a framework made of carbon nanotubes (CNTs) for cell and tissue engineering. In silico investigation of the electrical conductivity of the framework formed by T-junctions of single-walled carbon nanotubes (SWNTs) (12, 12) with a diameter of 1.5 nm has been carried out. A numerical evaluation of the contact resistance and electrical conductivity of seamless and suture T-junctions of SWCNTs is given. The effect of the type of structural defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Earlier, we studied the regularities of formation of protein–polymer matrices based on a network of SWCNTs, albumin, collagen, and chitosan [34]. In this paper, we study the regularities of formation of a layered protein–polymer matrix of three layers, including CNT-albumin, CNT-collagen, and CNT-chitosan layers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier, we studied the regularities of formation of protein–polymer matrices based on a network of SWCNTs, albumin, collagen, and chitosan [34]. In this paper, we study the regularities of formation of a layered protein–polymer matrix of three layers, including CNT-albumin, CNT-collagen, and CNT-chitosan layers.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we study the regularities of formation of a layered protein–polymer matrix of three layers, including CNT-albumin, CNT-collagen, and CNT-chitosan layers. For this, as in the previous study [34], we used the coarse-grained modeling method. Coarse-grained models of individual matrix layers are shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies demonstrated the importance of the type of structural defects in the contact area of b-SWCNTs on the contact resistance of the T-junction of SWCNTs in the resulting electrical conductivity of the final network [42]. A layered design was proposed using natural polymer matrices, i.e., collagen, albumin, or chitosan, connected via the b-CNTs to provide an electrically conductive network to assist cells in their mutual reconnection during the regenerative process [42].…”
Section: Theoretical Studiesmentioning
confidence: 99%